Epistaxis management at Guy's Hospital, 2009–2011: full audit cycles. Issue 1 (2nd December 2013) - Hall, A C; Simons, M; Pilgrim, G; Theokli, C; Roberts, D; Hopkins, C
Abstract: Objective: To assess management of epistaxis at a tertiary ENT referral hospital against a recently published standard of best practice. Methods: Fifty consecutive cases of acute epistaxis that required admission to Guy's Hospital in 2009 were evaluated. Epistaxis education sessions were held to introduce our algorithm of best practice in tandem with an emphasis on emergency department care. Similar retrospective reviews were carried out in both 2010 and 2011 (on groups of 50 patients). Results and conclusion: The first audit cycle demonstrated that only 8 per cent of patients underwent a suitable nasal examination in the emergency department prior to transfer, with no documented attempts at nasal cautery. Surgical intervention procedures were performed on only 40 per cent of eligible patients. The audit cycles that followed the introduction of the epistaxis algorithm demonstrated continued improvement in initial evaluation and management of epistaxis. In select patients, sphenopalatine artery ligation can provide timely, definitive management of refractory epistaxis.